Local high school closures and voter turnout: Evidence from East German municipalities - Mona Foertsch (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2024)
Do changes in public infrastructure impact voter turnout? After reunification numerous high schools have been closed in East Germany. Difference-in-differences estimations show that high school closures between 1992 and 2010 triggered a decline in voter turnout in the following state election, suggesting a sense of resignation among voters. However, this effect is not mirrored in national elections, indicating that voters do not extend their frustration to a higher level. The decline in voter turnout in state elections is rather short-living. This suggests that while voters may initially react to changes in local public infrastructure, they demonstrate resilience, at least in the medium term.
Keywords: D72; H40; R10; 330; Local schools; Elections; Voter turnout; Resilience; Germany